The future king - Schneider, Robyn (Schneider, Robyn. Emry Merlin, 2023)
Free to practice magic openly as the only female wizard in Camelot, Emry explores her powers are she grows closer to Prince Arthur, but when her magic grows increasingly dangerous and erratic, Emry turns to an eccentric alchemist for help.